Spy the lie former CIA officers teach you how to detect deception - Houston, Philip; Floyd, Michael; Carnicero, Susan (Icon Books Ltd, 2013)
Spy the Lie is a fascinating study of deception and a comprehensive lesson in how to identify and combat it. Featuring case studies based on the authors' real-life experiences in the field - involving 'turned' assets, KGB moles and criminal government officials - it reveals the methodology developed and used by the CIA to detect deception in the realms of counterterrorism and criminal investigation, and shows you how you can apply these techniques in your daily life. Whether hiring a new employee, investing money, knowing whether your boss is being straight with you, or finding out what your kids have been up to, this ingenious book will enable you to identify deceptive behavior in all its forms, and show you the techniques that will help you reach the truth.